Menstrual management and the impact of primary dysmenorrhea intensity on quality of life: A cross-sectional study in Chilean women - Julieta Aránguiz-Ramírez; Rossana Recabarren-Espinoza; Juana Mora-Lara (Medwave)
Introduction Primary dysmenorrhea is defined as pain during the menstrual cycle, recurrent cramping type in the absence of an identifiable cause. It can negatively affect the quality of life of those who suffer from it. The objective is to determine the association between pain intensity in primary dysmenorrhea and the impact on quality of life related to menstrual health, presenteeism, and sexual function in adult Chilean women.